Baseline anti-dsDNA concentrations and previous treatments predict response to Adalimumab and Etanercept: a retrospective investigation of 146 psoriasis patients - Hoffmann, Jochen; Knoop, Christian; Enk, Alexander; Hadaschik, Eva (Journal of dermatological science, 2014)
Background - Adalimumab and Etanercept are TNF-α antagonists commonly used for treatment of moderate-to-severe psoriasis and psoriatic-arthritis. Reliable instruments to assist the selection of patients for a specific treatment in a real-world scenario are unavailable. - Objective - To identify patient characteristics and baseline laboratory parameters predicting response to Adalimumab- and Etanercept-treatment. - Methods - We report a retrospective observational study including 116 and 64 psoriasis-patients treated with Adalimumab and Etanercept, respectively, at a dermatological outpatient clinic of a university hospital. Thirty four patients contributed data to both biologics. First occurrence of either loss-of-response or serious-side-effects (LOR/SSE) was chosen as clinical endpoint and predictors were identified using Cox-regression. - Results - Baseline anti-double-stranded DNA (anti-dsDNA) concentrations, number of previous treatments with TNF-α antagonists in general and previous treatment with Etanercept in particular significantly predicted LOR/SSE to Adalimumab. The predictive effect of baseline anti-dsDNA was conserved in TNF-α antagonist naïve patients. Number of previous systemic treatments other than TNF-α antagonists significantly predicted LOR/SSE to Etanercept. Age and baseline psoriasis area and severity index (PASI) did not predict response to either biologic in a clinically significant manner. - Conclusion - Our data suggests that treatment with Adalimumab may promise best results in psoriasis-patients with (A) low baseline anti-dsDNA concentrations, and (B) no previous TNF-α antagonist treatment. A clinically significant predictive effect of age and baseline PASI on response to Adalimumab and Etanercept is unlikely.
Gesehen am 21.10.2020